2006
DOI: 10.1063/1.2163339
|View full text |Cite
|
Sign up to set email alerts
|

Angular distributions of H-induced HD and D2 desorptions from the Si(100) surfaces

Abstract: We measured angular distributions of HD and D2 molecules desorbed via the reactions H+DSi(100)-->HD [abstraction (ABS)] and H+DSi(100)-->D2 [adsorption-induced-desorption (AID)], respectively. It was found that the angular distribution of HD molecules desorbed along ABS is broader than that of D2 molecules desorbed along AID, i.e., the former could be fit with cos(2.0+/-0.2) theta, while the latter with cos(5.0+/-0.5) theta. This difference of the angular distributions between the two reaction paths suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Looking at the angular distribution for a two-domain surface in the plane perpendicular/parallel to the dimer bonds containing the normal of the surface ͑like in the calculations of Inanaga et al and the available experimental results 1,4,5 ͒, it is shown that the angular distribution can be fitted with a cos 11.5 ͑ f −32°͒ + cos 11.5 ͑ f +32°͒ function, rather than with a cos 2 ͑ f ͒ function. Consequently, the angular distributions simulated with the LEPS PES developed by Kratzer and used by Inanaga et al are not in agreement with the measurements of Inanaga et al 1 or Bisson et al 4,5 Most likely, additional physical processes not covered by the LEPS PES contribute to these measured angular distributions.…”
Section: P Kratzercontrasting
confidence: 39%
“…Looking at the angular distribution for a two-domain surface in the plane perpendicular/parallel to the dimer bonds containing the normal of the surface ͑like in the calculations of Inanaga et al and the available experimental results 1,4,5 ͒, it is shown that the angular distribution can be fitted with a cos 11.5 ͑ f −32°͒ + cos 11.5 ͑ f +32°͒ function, rather than with a cos 2 ͑ f ͒ function. Consequently, the angular distributions simulated with the LEPS PES developed by Kratzer and used by Inanaga et al are not in agreement with the measurements of Inanaga et al 1 or Bisson et al 4,5 Most likely, additional physical processes not covered by the LEPS PES contribute to these measured angular distributions.…”
Section: P Kratzercontrasting
confidence: 39%
“…The reconstructed Si(001) surface is the most commonly studied, though studies including the reconstructed Si(111)-(7 × 7) surface suggest that the reaction mechanisms for H 2 adsorption are not strongly dependent on the details of the silicon surface . The dynamics of the reaction between hydrogen atoms and hydrogen-terminated Si(001) has been studied using periodic DFT and model potentials. This reaction has also been studied experimentally, using isotopic labeling. On the hydrogen-terminated Si(001) surface, the Eley–Rideal abstraction of H 2 occurs barrierlessly.…”
Section: Introductionmentioning
confidence: 99%
“…This potential accurately describes the geometry and the formation energetics of interstitial H in c-Si. 20,21 In order to further establish the reliability of the adopted force-field, we investigated the mobility of an isolated hydrogen atom in bulk c-Si and in a-Si, separately. In particular we evaluated its diffusivity D(T ) by calculating the corresponding mean square displacement and we obtained an activation energy for H migration of 0.44 eV (1.34 eV) in c-Si (a-Si).…”
mentioning
confidence: 99%